SISTEM PENGAMBILAN KEPUTUSAN PENENTUAN KARYAWAN TETAP DI SUMBER CIPTA MULTINIAGA DENGAN METODE TOPSIS - Dwi Rachmatulloh; Fauzan Natsir; Aswin Fitriansyah (IC Tech: Majalah Ilmiah, 2025)
This study aims to design and implement a decision-making system to determine permanent employees at PT Sumber Cipta Multiniaga using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. This system was developed to improve objectivity and transparency in the permanent employee selection process, taking into account various assessment criteria such as performance, discipline, integrity, and cooperation. The methods used include needs analysis, collection of employee criteria and alternatives data, and application of the TOPSIS algorithm to obtain mathematically and measurably ranked employee candidates. The results of the implementation show that the system is capable of producing accurate, efficient, and easy-to-use recommendations for permanent employees by management. The conclusion of this study states that the TOPSIS method is effective in supporting multi-criteria-based decision-making processes in determining permanent employees and can be applied to the selection process in similar companies.